Expert System Analysis of Divorce Case Handling in Islamic Law Using Breadth First Search Algorithm - Apdilah, Dicky; Harmayani, Harmayani; Salim Siregar, Emiel; Siregar, Aris; Andriani, Dian Ayu; Ikhwan, Ali; H Aly, Moustafa (ZERO: Jurnal Sains, Matematika dan Terapan, 2025)
Divorce is a separation between spouses often triggered by domestic violence, adultery, mental illness, gambling, or polygamy. Many first-time divorce plaintiffs are unaware of the proper legal procedures and tend to rush through the process. To address this, an expert system was developed using the Breadth First Search (BFS) algorithm to provide a more structured and measurable approach to divorce filing. The system aims to simplify and clarify the divorce procedure. The development process followed Rapid Application Development (RAD), with data collected through observations, interviews, and literature review. Experimental results with a sample of 100 users showed that 85% reported increased confidence in making decisions, the time to obtain accurate information decreased by 40%, and understanding of the divorce procedure improved by 90%. The system achieved a 92% user satisfaction rate, demonstrating its effectiveness. The BFS algorithm proved to be efficient and reliable, with statistically significant improvements in user experience.